The Religious Dimension in Development Studies - Loewen, Nathan (Bulletin for the study of religion, 2011)
Religion, spirituality and faith are themes gaining interest and prominence in the field of development studies. This "religious turn in development" (Pearson and Tomalin 2008, 49) has gone largely unnoticed by religious studies scholars. The range of current publications on the topic is not produced by self-identified religion scholars. I wish to give an overview of this nascent topic for study in order to suggest how the acumen of religious studies scholars might engage it. I will first make some remarks about the field of international development in order to locate challenges within the ‘religious turn’ within the current IDS discourse. I wish to conclude with some proposals for studying the religious dimensions of international development.